Spectroscopic evidence for NAT, STS, and ice in MIPAS infrared limb emission measurements of polar stratospheric clouds - Höpfner, M.; Luo, B. P.; Biermann, U.; Massoli, P.; Cairo, F.; Spang, R.; Snels, M.; Di Donfrancesco, G.; Stiller, G.; von Clarmann, T.; Fischer, H. (EGU, 2006)
We have analyzed mid-infrared limb-emission measurements of polar stratospheric clouds ( PSCs) by the Michelson Interferometer for Passive Atmospheric Sounding ( MIPAS) during the Antarctic winter 2003 with respect to PSC composition. Coincident Lidar observations from McMurdo were used for comparison with PSC types 1a, 1b and 2. Application of new refractive index data of beta-NAT have allowed to accurately simulate the prominent spectral band at 820 cm(-1) observed by MIPAS at the location where the Lidar instrument observed type 1a PSCs. Broadband spectral fits covering the range from 780 to 960 cm(-1) and from 1220 to 1490 cm(-1) showed best agreement with the MIPAS measurements when spectroscopic data of NAT were used to simulate the MIPAS spectra. MIPAS measurements collocated with Lidar observations of Type 1b and Type 2 PSCs could only be reproduced by assuming a composition of supercooled ternary H2SO4/HNO3/H2O solution ( STS) and of ice, respectively. Particle radius and number density profiles derived from MIPAS were generally consistent with the Lidar observations. Only in the case of ice clouds, PSC volumes are partly underestimated by MIPAS due to large cloud optical thickness in the limb-direction. A comparison of MIPAS cloud composition and Lidar PSC-type determination based on all available MIPAS-Lidar coincident measurements revealed good agreement between PSC-types 1a, 1b and 2, and NAT, STS and ice, respectively. We could not find spectroscopic evidence for the presence of nitric acid dihydrate ( NAD) from MIPAS observations of PSCs over Antarctica in 2003.